Women entrepreneurship: A sentiment analysis - Aam Slamet Rusydiana; Nadia Nurul Izza (Review of Islamic Social Finance and Entrepreneurship, 2022)
Purpose – This study aims to determine the sentiment towards women's entrepreneurship development in the last 32 years, from 1987 to 2019Methodology – The method used is descriptive statistical analysis combined with meta-analysis and sentiment from secondary data in metadata from 98 Scopus indexed publications, then processed using Microsoft Excel 2019 and SentiStrength software.Findings – The sentiment analysis results show that the expert opinions on the development of women's entrepreneurship are diverse, with positive sentiment at 30.6%, negative sentiment at 30.6%, and neutral sentiment at 38.8%. Based on the study results, it was found that there had been a rise in the study on the topic of developing women's entrepreneurship in the scholarly literature. Implications – These results can be used as illustrations to provide education and literacy about existing barriers to women's entrepreneurship. A strong commitment from a variety of stakeholders, including interested parties such as policymakers and the government, hoped to play a critical role in supporting and strengthening the women entrepreneurship ecosystem to advance economic empowerment by advancing innovation in tandem with the advancement of digitalization in the form of digital technology, improving the education system and employment practices can maximize the potential of female entrepreneurs, resulting in positive outcomes such as job creation and increased welfare, as well as assisting the United Nations in implementing the Sustainable Development Goals (SDGs).Originality – There are no papers discussing the evolution of global views of interest in women's entrepreneurship research using the sentiment method. Therefore, this paper is among the first.